2019
DOI: 10.1021/acschemneuro.9b00364
|View full text |Cite
|
Sign up to set email alerts
|

1-(2′,5′-Dihydroxyphenyl)-3-(2-fluoro-4-hydroxyphenyl)-1-propanone (RGM079): A Positive Allosteric Modulator of α7 Nicotinic Receptors with Analgesic and Neuroprotective Activity

Abstract: Acetylcholine7 nicotinic receptors are widely expressed in the brain, where they are involved in the central processing of pain, as well as in neuropsychiatric, neurodegenerative and inflammatory processes. Positive allosteric modulators (PAM) show the advantage of allowing the selective regulation of different subtypes of acetylcholine receptors without directly interacting with the agonist binding site. Here we report the preparation and biological activity of a fluoro-containing compound, 1-(2',5'-dihydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…This finding led to the evaluation of a collection of chalcones and related compounds, leading to the discovery of two new families of potent PAMs of the α7 nicotinic channels-polyhydroxychalcones [18] and polyhydroxydiphenyl propanones. This permitted the identification of a new chemotype of α7 nAChRs PAMs and compounds that exhibit promising analgesic and neuroprotective activities [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…This finding led to the evaluation of a collection of chalcones and related compounds, leading to the discovery of two new families of potent PAMs of the α7 nicotinic channels-polyhydroxychalcones [18] and polyhydroxydiphenyl propanones. This permitted the identification of a new chemotype of α7 nAChRs PAMs and compounds that exhibit promising analgesic and neuroprotective activities [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…RGM079 is another α7 nAChR PAM, which potentiated ACh-evoked currents without acting as an agonist in the absence of ACh. 42 Interestingly, ACh-induced currents in the presence of RGM079 decayed in a biphasic manner with a slow deactivation rate following a fast decay, indicative of RGM079 acting as a type I and type II α7 nAChR PAM. Further studies revealed that RGM079 was a promising drug candidate with acceptable pharmacokinetic properties, in vitro antioxidant and neuroprotective activities, and in vivo analgesic effect.…”
Section: Allosteric Modulations Of Ligand-gated Ion Channels (Lgics)mentioning
confidence: 95%
“…Thus, B-973 functions as a type II PAM of α7 nAChRs and also as an allosteric agonist at high concentrations. RGM079 is another α7 nAChR PAM, which potentiated ACh-evoked currents without acting as an agonist in the absence of ACh . Interestingly, ACh-induced currents in the presence of RGM079 decayed in a biphasic manner with a slow deactivation rate following a fast decay, indicative of RGM079 acting as a type I and type II α7 nAChR PAM.…”
Section: Allosteric Modulations Of Ligand-gated Ion Channels (Lgics)mentioning
confidence: 97%
“…In a clinical trial of phase 1b in 24 subjects with schizophrenia or schizoaffective disorder, AVL-3288 shows a lack of clinical effect. 13d Novel 3a (JNJ-1930942, mixed type I/II PAM, Figure 1), 15 3b (RGM079, mixed type I/II PAM, Figure 1), 16 and piperazine 4 (B-973, Ago-PAM, Figure 1) 17 were successively reported for the purpose of improved pharmacological activities in recent years. In addition, compound 1d is carried phase 1 clinical study (ref 9).…”
Section: ■ Introductionmentioning
confidence: 99%